Guilda de abelhas e outros visitantes de Matayba guianensis (Sapindaceae) em vegetação de cerrado - Carvalho, Ana Maria Coelho (2009)
In entomophilous plants, the most frequent flower visitors are social and solitary bees. The relationship is mutualistic, as bees benefit from pollen and nectar, and plants have their pollination performed by bees. The study of the guilds of flower-visiting bees presents as results, among others, the understanding of the guild structure and the factors that interfere with this structure. Among these, the deforestation of natural areas, as in the Cerrado , has been considered as one of the main factors. Thus, a common Cerrado plant Matayba guianensis Aubl., (Sapindaceae) was chosen, with the goal of studying the structure of the guild of flower-visiting bees in this species. Other objectives were: to investigate whether the environmental differences among three Cerrado areas would have an influence on the structure of this guild and determine the flower visitors and probable pollinators of Matayba guianensis, besides bees. Three Cerrado sites were chosen in the city of Uberlândia, Minas Gerais, Brazil: the Panga Ecological Station (EEP), with 1,011.90 a; the Palma da Babilônia Farm (FPB), with 444.79 a and the Souza Cruz (SC) Property, with 70.43 a. The areas presented environmental differences evinced by the estimates of natural vegetation in the surroundings: 52.62 % for EEP, 32.94 % for FPB and 9.73 % for SC. Bees and other insects were collected on Matayba guianensis in two consecutive flowering periods, from October to December of 2005 and 2006. Matayba guianensis presented asynchrony in its phenological stages and predominance of staminate individuals (64,7%) in comparison to the estaminate/pistilate and only pistilate individuals, and was considered a generalist species regarding its flower visitors. In the first phase, 1516 bees were collected, belonging to five families of Apoidea and to 80 species. Analyzing these, we found 30% of dominant and 46.3% of rare species. In the second phase, 562 bees, belonging to 66 species, composed of 15.2 % of dominant ones and 56.1% of rare ones, were collected. Overall, 2078 bees, pertaining to 105 species, were collected. The Apidae family stood out in terms of number of species and individuals. The most abundant species was Apis mellifera, which represented 41.9 % and 32.7% of the bees collected in the first and second phases, respectively, followed by Scaptotrigona depilis. The visitation pattern of these species is not indicative of resource sharing. The structure of the guild, with many rare species and few abundant ones, as much as the richness and abundance of the families of Apoidea, was similar to other studies conducted in the Cerrado region. The collecting of bees in a single plant species was capable of representing, at least partially, the richness of bees in the Cerrado . There was great similarity between the bee guilds in EEP and FPB. The composition of species of each guild varied more among the three areas than the richness and abundance. The comparison between the bee guilds collected in EEP in 1988/89 and 2005/2006 made the changes in abundance and composition of species evident. The proportion of natural vegetation, the location and the biology of each species, such as in the case of Melipona, are factors that influenced the structure of the bee guilds. Other flower visitors of Matayba guianensis were the Coleoptera, with 35 species, the Diptera, with 37 and wasps, with 54. Some of these species, as Ornidia obesa and Palpada sp.1, may act as pollinators. Other species are probably damaging the plant, as the phytophagous Coleoptera. Matayba guianensis is a key plant in the maintenance of guilds of bees as well as of other Cerrado insects.